Treatment adherence in newly diagnosed type 2 diabetes: patient characteristics and long-term impact of adherence on inpatient care utilization. Issue 4 (18th May 2016) - Sun, Peter; Lian, Jean
ABSTRACT: Objectives: The purpose of this study was to evaluate the impact of antidiabetic medication adherence on hospital utilization in patients with newly diagnosed type 2 diabetes mellitus (T2D). This study specifically analyzed patients with newly diagnosed T2D with the intent of lessening intragroup disease severity differences, and adjusting for a range of other clinical and demographic characteristics. Methods: This retrospective US claims database study evaluated adults with newly diagnosed T2D who started antidiabetic medications in 2005–2009, had ≥ 2 antidiabetic medication claims after their first (baseline). Medication adherence was evaluated using the medication possession ratio (MPR) of any or all antidiabetic medication(s) during the 3-year post-baseline period. Repeated-measures analyses examined changes in inpatient utilization from the pre- to post-baseline period. The impact of adherence on hospital utilization during the post-baseline period was evaluated with a logistic regression model to adjust for confounding factors. Results: The study included 192, 717 patients (mean age, 55.0 years). Mean MPR for antidiabetic therapy was 0.74. MPR was highest in elderly patients and Medicare beneficiaries. Mean annualized inpatient admissions during the 3-year post-baseline period were significantly lower in patients with MPR ≥ 0.80 (1.4) than in those with MPR < 0.80 (2.2; P  < 0.05). Logistic regression analysis, adjusting for patient characteristics and prior inpatient utilization, showed 39% lower odds of hospitalization (OR = 0.61; 95% CI = 0.534–0.693) for patients with MPR ≥ 0.80. People with T2D-related complications or hospitalization had approximately 2- to 3-fold higher risk of subsequent hospitalization. Conclusions: In newly diagnosed T2D patients with antidiabetic therapy in the first three ensuing years, higher antidiabetic medication adherence was significantly associated with lower hospital inpatient utilization before and after adjusting for patient characteristics.